Linda Gomez graduating CSU Fresno nursing program - Watkins, Howard K. (1977)
Front: Dawn Gomez, Doreen Gomez, Linda Gomez, Diane Gomez, Esther Fine, Rose Watkins; Back: ?, Howard Watkins, Pat Motts, Albert Watkins